Antimicrobial activity and additive effect of the modified Gingyo-san with antimicrobials against Helicobacter pylori. Issue 7 (July 2021) - Nakase, Keisuke; Nakanishi-Yamasaki, Mayu; Harada, Kanji; Koizumi, Juri; Yamada, Tetsuya; Ikoshi, Hideaki; Nakaminami, Hidemasa; Noguchi, Norihisa
Abstract: Introduction: Helicobacter pylori is an important factor in the development of gastroduodenal ulcers and gastric cancer. Although H. pylori eradication therapy has been employed, the eradication rate has decreased in recent years owing to an increase in clarithromycin-resistant strains. We previously reported the anti-infective effect of herbal medicines against several bacterial species. Here, we evaluated the growth inhibitory activity of herbal medicines alone and in combination with antimicrobials against H. pylori . Methods and results: Nine of 37 herbal medicines inhibited the growth of H. pylori ATCC700392. In particular, modified Gingyo-san showed the strongest growth inhibitory activity with a minimum inhibitory concentration (MIC) of 512 μg/ml for not only ATCC700392 but also clarithromycin-resistant strains having a 23 S rRNA mutation. Results of Time-Kill Kinetics Assay showed that 1 mg/mL modified Gingyo-san treatment for one hour killed 50% of the H. pylori population. Furthermore, modified Gingyo-san showed additive effects with clarithromycin, amoxicillin, and metronidazole against H. pylori ATCC700392 and clarithromycin-resistant strains. Conclusions: Our findings showed that modified Gingyo-san inhibits the growth of H. pylori and improves antimicrobial susceptibility when used in combination. Therefore, modified Gingyo-san has the potential to enhance the eradication rate of clarithromycin-resistant H. pylori .